Optimization of low-temperature catalytic cracking of polyolefin waste in open-batch reactors using zeolite beta with controlled intrinsic properties - Hankyeul Kang; Junghwa Yoon; Dongwoo Jun; Ki Hyuk Kang; Insoo Ro; Soohwa Jeong; Jong Hun Kang (Communications Engineering)
Abstract Environmental problems are worsening due to the complexity in managing plastic waste. Chemical recycling emerges as a pivotal technology that can suppress carbon introduction into the carbon cycle and provide petroleum alternatives for current petrochemical processes. The utilization of zeolites can reduce energy consumption by lowering the operation temperature for pyrolysis. Here, we demonstrate low-temperature catalytic cracking of polyethylene (PE) utilizing an open-batch reactor configuration and *BEA-type zeolite catalysts. With the optimized open-batch setup and zeolites, high PE conversion (~80%) and liquid selectivity (~70%) were achieved at 330 °C. We systematically explored the effects of aluminum (Al) site density and crystal size, revealing that zeolite crystal size is another critical factor determining the liquid production. This work not only demonstrates that an effective combination and optimization of reactor and catalysts can enhance the overall catalytic activity but also offers insights into designing catalysis systems for effective recycling of polyolefin wastes.